Development and characterization of Ruta graveolens L. extract-loaded polymeric microparticles for vehicle in children's shampoo formulation (Research, Society and Development, 2023)
The aim of the present study was to develop, to characterize and to quantify Ruta graveolens L. extract-loaded poly(ԑ-caprolactone) microparticles for application in a children's shampoo for the safe combat of pediculosis. The hydroalcoholic extract was obtained from the dried plant through the turbolysis method. Microparticles were obtained by the emulsification solvent evaporation technique, modifying the proportion of extract and polymer. The polymeric systems were characterized through morphological and spectroscopic studies. The encapsulation efficiency was verified by the indirect method of quantification. A children's shampoo formulation was developed, verifying the organoleptic and physical-chemical characteristics. The polymeric microparticles were successfully obtained by the chosen method and showed an average yield of 49.7% and encapsulation efficiency above 82.26%. The systems had a spherical shape and smooth edge, average size between 686.9 and 2973.6 nm, low polydispersion index and negative zeta potential. Infrared spectra demonstrated distinct bands for isolated materials compared to microparticle formulations. The developed children's shampoo formulation presented white coloration and fragrance and texture consistent with the shampoo formulation. The density found was 1.0025 g/mL and viscosity of 47.78 cP, while the pH of the formulation was close to the tear pH. Thus, the present study successfully obtained R. graveolens L. extract-loaded PCL microparticles and effectively developed a children's shampoo formulation for microparticles vehiculation to use as a safe alternative for the treatment of pediculosis.